Adopting a patient‐centred approach: an investigation into the introduction of bedside handover to three rural hospitals. Issue 13 (24th October 2013) - Bradley, Stacey; Mott, Sarah
<x xml:space="preserve">Abstract</x> Aims and objectives To study empirically the process and outcomes of the implementation of nurse‐to‐nurse bedside handover in three rural South Australian hospitals. Background While the importance of handover is identified in literature, little is written about its implementation. It is, however, suggested that bedside handover is a more patient‐focussed approach than others available. Design A mixed‐method, pretest post‐test evaluative approach involving quasi‐experimental and ethnographic elements was used. The self‐selected sample comprised nine inpatients (five women, four men) and forty‐eight self‐selected enrolled/registered nursing staff (forty‐seven women, one man) from three acute hospital wards in rural South Australia. Lewin's (Human Relations, 1, 1947a, 2; Readings in Social Psychology. Henry Holt, New York, 1947b, 197) 3‐stage model of change provided a theoretical basis and structure for the study. Methods Patient perceptions were obtained using ethnographic interviewing. Staff perceptions of patient involvement were obtained through questions rated on a 7‐point Likert scale and ethnographic interviewing. Results Results indicated that patients preferred the bedside handover method over the traditional closed‐door office handover approach. The key differences (as defined by patients) are that the bedside handover process incorporates social aspects for the patient, patients have the opportunity to know who is looking after them and patients are included in discussion related to their care. Furthermore, results suggest that staff believed the level of patient involvement in their care had increased under the bedside handover process. Conclusions The results demonstrate that both patients and staff perceive patients to be more involved in their care under the bedside handover approach. The literature notes a recent move towards adopting patient‐centred care approaches in clinical settings and the many benefits associated with this style of care. This study has proven that implementing bedside handover has resulted in a patient‐centred approach. Relevance to clinical practice This study generates further knowledge about rural nursing and contributes insight into the importance of handover implementation method – areas that are not widely documented in existing literature.